Linear and branched polyacrylates as a delivery platform for peptide-based vaccines. (September 2016) - Chandrudu, Saranya; Bartlett, Stacey; Khalil, Zeinab G; Jia, Zhongfan; Hussein, Waleed M; Capon, Robert J; Batzloff, Michael R; Good, Michael F; Monteiro, Michael J; Skwarczynski, Mariusz; Toth, Istvan
Aim: Peptide-based vaccines are designed to carry the minimum required antigen to trigger the desired immune responses; however, they are usually poorly immunogenic and require appropriate delivery system.Results: Peptides, B-cell epitope (J14) derived from group A streptococcus M-protein and universal T-helper (PADRE) epitope, were conjugated to a variety of linear and branched polyacrylates. All produced conjugates formed submicron-sized particles and induced a high level of IgG titres in mice after subcutaneous immunization. These polymer–peptide conjugates demonstrated high opsonization capacity against group A streptococcus clinical isolates.Conclusion: We have successfully demonstrated that submicron-sized polymer–peptide conjugates were capable of inducing strong humoral immune responses after single immunization.